EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DALAM MANINGKATKAN PEMBANGUNAN FISIK DESA SEPONTI JAYA KECAMATAN SEPONTI KABUPATEN KAYONG UTARA - Tina Marliana; Bambang Genjik; Maria Ulfah (Universitas Tanjungpura, 2021)
AbstrakThis study aims to determine the effectiveness of Village Fund Allocation management in improving the physical development of Seponti Jaya Village, Seponti District, Kayong Utara Regency, which includes planning and monitoring of village fund allocation management. This research uses qualitative methods in descriptive form. Data collection tools used observation guides, interviews, and documentation. The results showed; 1) the village government of Seponti Jaya has implemented a village fund allocation management plan in accordance with the regulation of the North Kayong Regent regarding technical guidelines for the use of village funds in Kayong Utara district in 2018; 2) the supervision of the management of the Village Fund Allocation is not good due to the lack of supervision from government officials and not including legal officers in the management of Village Fund Allocation; 3) planning for the management of the Village Fund Allocation has been effective, while the supervision of the management of the Village Fund Allocation is ineffective. The physical development of the village has increased with the Village Fund Allocation every year, the Seponti Jaya Village government plans the physical development of the Village to facilitate the activities of the Village community.Keywords: effectiveness, Village Fund Allocation Management, Physical Development